MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPTITION SISWA KELAS XA SMA NEGERI 5 MERANGIN - Ahde Fitri; Vini Elvianita (Pendidikan Matematika | Universitas Merangin, 2016)
This research was motivated by the low mathematical problem solving abilities of students on the subject of Trigonometry. This is because students lack the interest and motivation to learn, the teacher still applies conventional learning models. Where learning activities are still centered on the teacher and students are less active and tend to be saturated when the learning process takes place. Based on the background of the problem, this study aims to Improve Students' Mathematical Problem Solving Ability through the Auditory Intelectually Repetition learning model of class XA students of SMA 5 Merangin year 2013/2014 lessons. The method of this research is classroom action research (CAR) conducted in class Xa of SMA 5 Merangin 2013/2014 academic year. The study was conducted in April 2014 with 3 cycles. The object of research is learning the subject of Trigonometry. The subjects of this study were class Xa students of SMA 5 Merangin in the academic year 2013/2014 totaling 28 students 17 male students and 11 female students. Data is collected using written test techniques and observations of students during the learning process. The results of this study indicate that the mathematical problem solving abilities of class Xa students of SMA 5 Merangin in the academic year 2013/2014 increased by using the Auditory Intelectually Repetition learning model. This increase can be seen from the results of the initial test (pre-test) indicating that only 31, 9%. After being given the Auditory Intelectually Repetition learning model there was an increase from the first cycle of 53.57% to 57.14% in the second cycle, and in the third cycle it increased to 75%. Increasing students' mathematical problem solving abilities also followed changes in student behavior. Based on the results of observations on the actions of the first cycle, cycle II and cycle III, there was an increase in student activity. Activity increased from an average of 45.06% in the first cycle to 53.97% in the second cycle and 72.03% in the third cycle.